2018
DOI: 10.1021/acs.iecr.7b04435
|View full text |Cite
|
Sign up to set email alerts
|

Novel MILP Scheduling Model for Power-Intensive Processes under Time-Sensitive Electricity Prices

Abstract: In this work, a mixed-integer linear programming (MILP) model is presented based on a discrete-time scheduling formulation that allows modeling and optimizing operational decisions for processes working under time-sensitive energy prices. The main goal is to find an optimal production schedule, over a given time horizon, that satisfies product demand while minimizing total energy cost. This novel formulation, based on a new concept to model the transitions between alternative operating modes, is very efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…The electrolyte is collected in a tank (4) where it is constantly stirred (8) to disperse the oil phase in the water phase. The tank's temperature is monitored using a thermostat (7). Possible ACN vapor is condensed using a reflux condenser (5), while noncondensable gases produced at the electrodes may leave the system through the vent.…”
Section: Flexibility Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrolyte is collected in a tank (4) where it is constantly stirred (8) to disperse the oil phase in the water phase. The tank's temperature is monitored using a thermostat (7). Possible ACN vapor is condensed using a reflux condenser (5), while noncondensable gases produced at the electrodes may leave the system through the vent.…”
Section: Flexibility Experimentsmentioning
confidence: 99%
“…This is particularly true for electrochemical processes due to their high demand for electrical energy and a considerable share of electricity cost in the production costs . If companies participate in these new markets, either plants are operated at high capacity in the case of low electricity prices and at low capacity in the opposite case or a load reduction/increase is offered to the transmission system operators (TSOs) for stabilizing the power grid . Such operating modes are expected to become even more important in the future as the installed capacity of fluctuating renewables in the electricity mix and the electrification of transport and heating continue to increase, whereas base-load power plants, such as coal-fired power plants, are being more and more decommissioned, thus creating the need for additional flexibility and storage capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Contributions of the first type include general frameworks, 9–11 and applications to processes such as polymerization 12 and air separation 13 . In the second approach, to balance computational efficiency and quality of the obtained schedules, the concept of mode is used to model transient operations 14–17 . However, the use of modes allows only restricted modeling of dynamic operations.…”
Section: Introductionmentioning
confidence: 99%
“…Compressor systems consume large amounts of electricity to raise the pressure high enough to achieve cryogenic temperatures for distillation. Due to the recent volatility in energy markets, there is a significant opportunity to reduce costs by taking advantage of lower electricity price periods. As shown in many recent works on industrial DSM, considering time-sensitive electricity prices can have a significant impact on the load profiles of power-intensive industrial processes. For more details on industrial DSM, a comprehensive literature review can be found in Zhang and Grossmann, where air separation works are listed with their main model features.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed a multiscale multistage stochastic programming MILP model. Recently, Basán et al proposed a novel, efficient, and robust formulation, based on a new concept to model the transitions between alternative operating modes called the Process State Transition Network (PSTN). The model was also used to efficiently solve a real-world industrial case study, providing optimal solutions with modest computational effort when considering directed transitions, and it only covered the external liquefier of an air separation plant.…”
Section: Introductionmentioning
confidence: 99%